A serum-based DNA methylation assay provides accurate detection of glioma. Issue 9 (9th February 2021) - Sabedot, Thais S; Malta, Tathiane M; Snyder, James; Nelson, Kevin; Wells, Michael; deCarvalho, Ana C; Mukherjee, Abir; Chitale, Dhananjay A; Mosella, Maritza S; Sokolov, Artem; Asmaro, Karam P; Robin, Adam; et al.
Abstract: Background: The detection of somatic mutations in cell-free DNA (cfDNA) from liquid biopsy has emerged as a noninvasive tool to monitor the follow-up of cancer patients. However, the significance of cfDNA clinical utility remains uncertain in patients with brain tumors, primarily because of the limited sensitivity cfDNA has to detect real tumor-specific somatic mutations. This unresolved challenge has prevented accurate follow-up of glioma patients with noninvasive approaches. Methods: Genome-wide DNA methylation profiling of tumor tissue and serum cfDNA of glioma patients. Results: Here, we developed a noninvasive approach to profile the DNA methylation status in the serum of patients with gliomas and identified a cfDNA-derived methylation signature that is associated with the presence of gliomas and related immune features. By testing the signature in an independent discovery and validation cohorts, we developed and verified a score metric (the "glioma-epigenetic liquid biopsy score" or GeLB) that optimally distinguished patients with or without glioma (sensitivity: 100%, specificity: 97.78%). Furthermore, we found that changes in GeLB score reflected clinicopathological changes during surveillance (eg, progression, pseudoprogression, and response to standard or experimental treatment). Conclusions: Our results suggest that the GeLB score can be used as a complementary approach to diagnose and follow up patients with glioma.